Estudo da associação do polimorfismo genético em carcinomas da tiróide - REIS, Angela Adamski da Silva (2010)
Thyroid nodules are common in clinical practice and the incidence of thyroid cancer is increasing throughout the world. Certainly, an important factor for the increase of the incidence is the use of ultrasound and PAFF. The identification of genetic polymosphism is important for understanding the potential mechanisms involved in thyroid carcinogenesis. We hypothesized that polymorphisms of xenobiotic enzyme system (CYP1A1, GSTM1 and GSTT1) and the common germline polymorphism of TP53 gene at codon 72 may be associated with the risk of thyroid cancer. To evaluate the role of such polymorphisms, we investigated 122 cases of thyroid nodules, classified according to the following: 35 malignant neoplasic nodules (MNN), 20 benign neoplasic nodules (BNN) and 67 non-neoplasic nodules (NNN) compared with 134 controls of the healthy individuals randomly selected. The PCR-RFLP was used in the analysis of the CYP1A1m1 and CYP1Am2 genotypes; the multiplex PCR was used in the deletion analysis of the GSTM1 and GSTT1; and for the determination of the polymorphism in the gene TP5372, the samples were submitted to conventional PCR reaction. We included case-control studies that compare the incidence of germline polymorphism of TP5372 in patients with thyroid cancer by DerSimonian-Laird method. Our results demonstrated that CYP1A1m1 and CYP1A1m2 genotypes were frequent not only as neoplasic thyroid nodules and non-neoplasic thyroid nodules but also in the control group, which suggests that those are not associated with thyroid nodules. The null genotype for the GSTT1 gene was predominant in benign nodules compared with the control group (p<0,005) indicated that individuals that possess such null genotypes presented a predisposition to benign thyroid diseases than malignant. The risk analysis, done by Odds Ratio, suggests that the risk genotypes GSTM1 (OR=12,82; p=0,004) and GSTT1 (OR=4,53; p<0,0001) contribute to the development of the BNN and NNN, respectively. The frequency of the p53 Arg allele was significantly higher in both patient and control groups. The genotype p53Arg Arg presents a lower risk to thyroid cancer, indicating that the allele arginine in homozygosis can present a protective effect against thyroid carcinogenesis (OR: 0.15; p<0.0001). The data of the meta-analysis demonstrates that the relation between the genotype and phenotype from the TP5372 polymorphism is not associated with the genetic susceptibility at thyroid cancer. The high incidence of thyroid pathologies among women is a characteristic not completely understood. Therefore, some factors, such as the imbalance of sexual hormones; nutritional deficiencies, especially in iodine; therapeutic exposure to radiation; failures in the control systems of the cellular cycle; and the genetic polymorphism could explain the high incidence of thyroid disease among women. Although the interindividual variation in the susceptibility to thyroid diseases could indicate new perspectives to an early diagnostic and prognostic, the polymorphic profile requires additional studies.